Emerging ≈800 nm Excited Lanthanide‐Doped Upconversion Nanoparticles. Issue 6 (16th December 2016) - Xie, Xiaoji; Li, Zhanjun; Zhang, Yuanwei; Guo, Shaohong; Pendharkar, Aarushi Iris; Lu, Min; Huang, Ling; Huang, Wei; Han, Gang
Abstract : Lanthanide‐doped upconversion nanoparticles can tune near‐infrared light to visible or even ultra‐violet light in emissions. Due to their unique photophysical and photochemical properties, as well as their promising bioapplications, there has been a great deal of enthusiastic research performed to study the properties of lanthanide‐doped upconversion nanoparticles in the past few years. Despite the considerable progress in this area, numerous challenges associated with the nanoparticles, such as a low upconversion efficiency, limited host materials, and a confined excitation wavelength, still remain, thus hindering further development with respect to their applications and in fundamental science. Recently, innovative strategies that utilize alternative sensitizers have been designed in order to engineer the excitation wavelengths of upconversion nanoparticles. Here, focusing on the excitation wavelength at ≈800 nm, recent advances in the design, property tuning, and applications of ≈800 nm excited upconversion nanoparticles are summarized. Benefiting from the unique features of ≈800 nm light, including deep tissue penetration depth and low photothermal effect, the ≈800 nm excited upconversion nanoparticles exhibit superior potential for biosensing, bioimaging, drug delivery, therapy, and three dimensional displays. The critical aspects of such emerging nanoparticles with regards to meeting the ever‐changing needs of future development are also discussed. Abstract : Shifting the upconversion excitation wavelength to a biological "sweet spot" at 800 nm offers opportunities for the further development of lanthanide‐doped upconversion nanoparticles. Recent advances in the emerging ≈800 nm excited upconversion nanoparticles, ranging from design principles and property tuning, to their current applications and future development, are discussed.